Women with Pain due to Osteoarthritis: The Efficacy and Safety of a Once-Daily Formulation of Tramadol - Kean, Walter F.; Bouchard, Sylvie; Roderich Gossen, E. (Pain medicine (Malden, Mass.), 2009)
ABSTRACT Objective.  This analysis assesses the efficacy and safety of treatment with a once‐daily oral formulation of tramadol for up to 12 weeks compared with placebo in women with moderate‐to‐severe pain due to osteoarthritis of the knee. Design.  Two parallel, placebo‐controlled phase III clinical trials were analyzed; patients were randomized to a fixed dosage of Tramadol Contramid® once a day (OAD) 100, 200, and 300 mg daily, or placebo. Outcome Measures.  The primary efficacy end points were the percentage difference from baseline of the Western Ontario and McMaster University Osteoarthritis Index (WOMAC) subscale scores for pain and physical function, and the patient global rating of pain relief after 12 weeks of maintenance therapy. Results.  The analysis included 405 women receiving tramadol and 280 receiving placebo. At week 12, 179 of 204 women (87.7%) receiving tramadol rated their overall pain relief as effective or very effective compared with 134 of 177 (75.7%) receiving placebo. A time‐weighted analysis revealed statistically significant improvements over placebo for all the WOMAC subscale scores across all three dosages. The percentage improvements from baseline of the WOMAC pain scores were significantly better than placebo for the 100‐mg (58.8 ± 37.1%, P = 0.018) and 300‐mg (58.9 ± 38.8%, P = 0.023) treatment arms; however, the 200‐mg dosage was not significant (53.0 ± 38.5%, P = 0.175). The WOMAC physical function scores showed significant improvement for the 100 (56.9 ± 36.4%, P = 0.009), 200 (54.0 ± 33.8%, P = 0.034), and 300 mg (53.4 ± 41.4%, P = 0.043) daily dosages. Conclusion.  For moderate‐to‐severe pain due to osteoarthritis of the knee, women experience significant analgesia and improvement of physical function over time with treatment with Tramadol Contramid® OAD.